Actividades didácticas y su impacto en el desarrollo cognitivo en los niños de Educación Inicial II - Briones Contreras, Mariuxi Maricela (2025)
The present research, entitled "Didactic activities and their impact on cognitive development in children in Early Childhood Education II." Didactic activities are pedagogical strategies designed and planned by teachers in order to promote meaningful learning and the integral development of students. The objective of this study was to determine the impact of didactic activities on cognitive development in children in Early Childhood Education II, of the "Emigdio Esparza Moreno" Educational Unit. The problem addressed was to overcome the limitations in the implementation of didactic activities that promote cognitive skills such as attention, memory, language and problem solving in children. The methodology used was qualitative, descriptive, non-experimental, applying analytical-inductive methods; the sample was 2 teachers and 28 children. Interview and observation techniques were used to evaluate the impact of didactic activities. The results of the interview show that teachers recognize the importance of didactic activities, and their implementation faces obstacles such as the lack of adequate spaces and resources. Likewise, in the observation, little motivation was evident in the children before starting the activities, which results in difficulties to concentrate, difficulties in language, teamwork, problem solving and developing motor coordination. It is concluded that it is essential to strengthen the implementation of innovative and varied didactic activities that capture the interest of children and respond to their learning needs, thus ensuring optimal cognitive development in the Initial Education II stage.